Implementing STARTALK-endorsed principles in an intensive summer LCTL program: Challenges and implications - Chen, Julian; Jourdain, S. (2015)
This paper discusses how STARTALK-endorsed principles were adopted in a first-year STARTALK summer program in three LCTLs: Arabic, Persian and Turkish. Our 34 high school and college participants were enrolled in seven week, six-credit intensive introductory college courses. All students began at the Novice-low proficiency level in each LCTL. The program effectiveness was assessed by students’ learning outcomes (ACTFL-based proficiency test results and LinguaFolio evidence) and evaluated by a site visit team’s observation report, program exit surveys and student project work. Students’ oral proficiency scores showed a significant improvement ranging from the Novice level to Intermediate low/high. Triangulation of the qualitative data also revealed overall positive attitudes toward this immersive and learner-centered program that integrated language, culture, and content in LCTLs. Positive results did not come without some challenges in curriculum design and technological integration. Lessons learned and pedagogical implications are provided for others interested in implementing similar programs.